Comparative Analysis of Costs Between the Use of PLN Electricity and PV Rooftop for 30/60-Type House in Sukabumi, Indonesia - Heliani; Herdina, Vina; Ali, Mukhlis (Nusantara Science and Technology Proceedings, 2020)
Housing development in Indonesia, especially in Sukabumi, in the last few years, many simple houses of type 30/60 have been built as a type of simple house that has received subsidized KPR facilities and is the type of house most sold in Indonesia. The problem studied in this study is that there is no incentive provided by the government to encourage the use of PV Rooftops. This study aims to see a comparison in the process of using PV rooftops with the installation of PLN electricity in the Home Ownership Credit (KPR) scheme, especially for subsidized KPR, which is the prima donna of housing in Indonesia today. So that it can provide input on what incentives should be done by the government. The method used is a comparison of the life cycle costs between the use of PLN electricity and PV Rooftop. From the results of the cost analysis carried out financially, this design has not been profitable from a financial point of view due to the high credit interest rate, namely 10%. Therefore, there needs to be a credit interest subsidy so that it can decrease to 5% -8% to obtain benefits compared to the use of electricity from PLN.